The Influence of Specimen Misalignment on Wear in Conforming Pin on Disk Tests - Garcia-Prieto, I.; Faulkner, M. D.; Alcock, Jeffrey R. (Elsevier Science B.V., Amsterdam., 2004)
A pin-on-disk test apparatus was modified to decrease the degree of misalignment between the pin end and the disk counterface. This was achieved by separate alignment of both pin and disk. Disk alignment was allowed by incorporating a kinematic three-ball arrangement into the disk under-face. A self-aligning pin alignment system was introduced which did not require the perpendicularity of the pin to be measured. The unmodified system had an alignment within that permitted by the ASTM G99-95a standard. However, the modified, and improved, alignment system produced significant changes in recorded wear behaviour in comparison with the unmodified system. The standard deviation of the wear data was considerably reduced and the correlation of the wear data with applied load significantly improved. The modified alignment also reduced the absolute value of wear recorded. This effect was observed for both wear volume assessed from mass change and wear volume assessed from pin height change. The reduced constraint of a misaligned pin in comparison with that of a well-aligned pin may account for the difference in these results.
Keywords: Pin-on-disk; Reproducibility; Alignment; Wear volume